MANAJEMEN SDM PERANGKAT DESA DAN DAMPAKNYA TERHADAP PERTUMBUHAN UMKM DI INDONESIA - Zaman, Nur; Octo, Cindy Wulandari; Dhora, Sony Tian; Yuliaty, Farida; Prasetyo, Iwan (KOMITMEN: Jurnal Ilmiah Manajemen, 2022)
The development of micro, small, and medium-sized enterprises (MSMEs) in Indonesia requires support from the Indonesian government at all levels, beginning with the village government. This assistance can only be provided in an effective manner if the governing body of the village is comprised of village officials who possess a strong and dependable work ethic. In order to accomplish this objective, the apparatus of the village will require management of its human resources. This study's objective is to investigate the evolution of village apparatus human resource management and its bearing on the expansion of micro, small, and medium-sized enterprises (MSMEs) in Indonesia. This investigation takes a qualitative approach and makes use of descriptive research methods. According to the findings of the study, village apparatuses have the potential to advance micro, small, and medium-sized enterprises (MSMEs) by reforming the bureaucracy in the village with human resource management. The process entails planning, recruitment, selection, training and development, as well as performance evaluation and evaluation of progress. Regarding the development of micro, small, and medium-sized enterprises (MSMEs), the local government of the village can act as a facilitator, a regulator, or a catalyst, each of which has a very significant influence.